Correlation between upper airway morphological changes and jaw movement after bimaxillary orthognathic surgery in patients with skeletal Class Ⅲ malocclusion - LI Gen, GUO Songsong, CAI Guanhui, SUN Lian, SUN Wen, WANG Hua (Editorial Office of Stomatology, 2024)
Objective To investigate the morphological changes in the upper airway after bimaxillary surgery in patients with skeletal Class Ⅲ malocclusion and the relationship between jaw movement and airway changes using CBCT. Methods This study involved 44 individuals(21 males and 23 females)receiving Class Ⅲ bimaxillary surgery. Preoperative and 3-6-month postoperative CBCT data were examined using Dophin3D 11.95 software. The alterations before and after upper airway surgery were analysed using paired t-test and non-parametric Wilcoxon rank sum test. The association between airway alterations and jaw movement was examined using Pearson's correlation coefficient. Results Patients who underwent Class Ⅲ bimaxillary surgery had significantly reduced upper airway volume, sagittal cross-sectional area, and minimum cross-sectional area(P<0.01). A correlation exists between oropharyngeal volume change and point B change(P<0.05). When B point recession was >7 mm, the decrease in upper airway volume increased significantly(P<0.01), as did the risk of minimum cross-sectional area of the patient's airway(P<0.01). Conclusion Class Ⅲ bimaxillary surgery reduces upper airway capacity. Postoperative reduction in upper airway capacity coincides with mandibular recession. Mandibular recession(>7 mm)may reduce postoperative upper airway capacity and increase the risk of OSAHS. Patients at risk of upper airway stenosis should have their protocol modified to reduce airway risk.